The economics of COVID-19 - Baltagi, Badi H.; Moscone, Francesco; Tosetti, Elisa (Contributions to economic analysis ;, 2022)
The global health crisis, exacerbated by the COVID-19 outbreak, has challenged all sectors of society, including health, economics, finance, and social inequality. The threats and complexities from the COVID-19 pandemic shock are the core subject of this latest volume in the Contributions to Economic Analysis series. The Economics of COVID-19 contains selected contributions analysing the effects of this pandemic, covering macroeconomics, computable general equilibrium models, financial markets, the reduction in seismic noise due to the slowdown in traffic and economic activities caused by the spread of the virus, the rapid surge in the digital transformation of production and consumption. Also included are health studies proposing to improve the traditional epidemic models, the effects of the pandemic on mental health, Minority Ethnic Groups in the UK, as well as the Lombardy region in Italy. The aim of this collection is to spur much needed research into the effects of COVID on the global economy, the health, and financial sectors, as well as its effects on development and growth and economic inequality.